Analisis SWOT untuk Strategi Pengembangan Objek Wisata Geopark Silokek di Nagari Silokek oleh Dinas Pariwisata Pemuda dan Olahraga Kabupaten Sijunjung - Nada Zahrani; Adil Mubarak (Dinasti Research, 2022)
This study aims to analyze the strengths, weaknesses, opportunities and threats in the strategic efforts to develop the Silokek Geopark tourist attraction in Nagari Silokek, Sijunjung Regency. Then the application is analyzed in carrying out development by minimizing weaknesses and threats, and optimizing the usability of opportunities and strengths. Data was collected through literature studies, observations and also interviews with the Youth and Sports Tourism Office, Pokdarwis, local communities, and visitors. The data were analyzed in a descriptive way, then in carrying out an analysis of the application of the strategy for developing the Silokek Geopark tourist attraction, it was carried out through a SWOT analysis. Based on the research results, it can be concluded that the strategy in developing the Silokek Geopark tourist object is optimizing programs by utilizing the potential of the Silokek Geopark, utilizing communication and telecommunications technology in an effort to maximize promotion, improve the management of tourist attractions so that investors are interested in investing their shares in Silokek Geopark tourist object in Silokek Nagari.